The role of ferroptosis in the treatment and prognosis of malignant melanoma - Yuqing WANG; Fangqi CHEN; Juanmei CAO; Ting WU; Yan LIANG; Yifan JIN; Jinshan ZHAN; Changzheng HUANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Malignant melanoma (MM) is a highly malignant tumor of melanocytes, with increasing mortality rate and incidence rate in recent years. Although the treatments with targeted therapies and immune checkpoint inhibitors have significantly improved survival in advanced MM, tolerance and futile treatment are still the problems in the management of MM. Ferroptosis is a newly identified form of iron-dependent regulated cell death, which dysregulation is related to MM. This paper reviews the role of ferroptosis in the treatment, metastasis and prognosis of MM, and provides a reference for the treatment and future research in MM.